Adapting fairy tales through an Islamic lens: a study of Gilani-Williams’ Cinderella: an Islamic tale - Hasan, Md. Mahmudul; Abdul Hamid, Nor Adilah; Ramlan, Wan Nur Madiha (Ediziani Universita di Macerati Italy, 2020)
Fairy tales contain allegorical plots that portray real life events and are powerful enough to shape people’s attitudes. However, some elements included in them may not be appropriate for young readers who have not developed a sufficient moral compass to differentiate the good from the bad. In order to protect children from untoward influences, it is perhaps important to adapt the plots by making some amendments, removing and replacing the not-so-relevant elements with ones that suit children’s imaginations and promote good values. Hence, Fawzia Gilani-Williams brings in Islamic perspectives in children’s literature. She seeks to produce alternative versions of tales to make them compatible with Islamic teachings and appropriate for children. In this paper we examine her Cinderella: An Islamic Tale (2010) and compares her adapted story with Perrault’s Cinderella (1697).